Unposted letter - "Ra, Voice" (Chennai, 2002)
The rise and fall of every human being has its effect on the overall human consciousness. Every lesson learnt, every mistake committed, every error corrected, every discovery, every invention, every insight, every idea, every revelation, every talent unfolded, every limit redefined, every thought released, every vibration experienced$1! = (Bby every individual paints yet another stroke in the evolution of human consciousness. When 'a' man lives his life with heightened awareness, his life helps humanity to gain a few years of maturity without having to live those few years. In effect, he fast-forwards humanity by a few years. Every being who is living his life with heightened awareness is actually doing God's work$1! = (Bhe has been delegated a responsibility by Existence to play a part in evolving human consciousness$1! =s
Keywords: Hapiness-Religious aspects